Prevalence and isolation frequency of pathogenic strains responsible for some infections in Bechar’s community (Southwest of Algeria): About 1458 cases. (Bangladesh Journal of Medical Science, 2020)
Background: The microbial infections represent a real public health problem with considerable individual and economical consequences. Their surveillance has become, in recent decades, an essential element of any program to control these infections.Aim: In this study, we estimated the prevalence and frequencies of some microbial infections amongst the Bechar’s community (Algeria).Methods: The microbiological analyzes of various pathological samples namely : urine and vaginal discharge, pus, nipple discharge, originally sampled from throat, otitis discharge and effusion liquid, have been carried out in the medical analysis laboratory of Bechar for seven months.Results: The obtained results showed that out of 1458 samples, 506 cases were positive (34.7 %), for some infections, there is a relationship correlation between the infections’ frequency and their prevalence with the age and gender of patients, as factors; which the female gender presents 74.7 % of positive cases, a sex-ratio less than 1; besides, the most affected population is aged between 25 and 39 years old. The isolated microbial species, which are the most incriminated agents responsible for the studied infections, were mainly Escherichia coli with an isolation frequency of 87.15 %, followed by coagulase-positive Staphylococci CoPS (5.13 %), Streptococcus sp (3.16 %), fungal species Candida albicans (1.58 %), Coagulase-negative Staphylococci Co NS (1.18 %). However, less than 2 % of infectious agents were recorded for the bacterial strains P. aeruginosa, K. pneumoniae and Enterococcus sp.Conclusion : This study can provide a platform for an effective prevention strategy and can be useful for epidemiological prediction with a decision-making.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.404-413